MAC OS X Leopard : beyond the manual - Lee, Mike (Springer, 2017)
Good computer books make assumptions about the reader: what they do and don't know when they pick up the book, and what they want to know when they put it down. For each reader this could be very different; therefore, a book that suits one person may not be the best for another. Mac OS X Leopard: Beyond the Manual makes some assumptions too, ones that tend to differ from other Mac OS X books.